Literature Review of E-Learning, Blended Learning, and Hybrid Learning and Their Implementation in Physics Learning - Siregar, Winda Sari; Sinaga, Josua Anly Hendra; Simamora, Peronika; Simanjuntak, Mariati Purnama (Schrödinger: Journal of Physics Education, 2025)
Purpose of the study: This study aims to analyze the implementation, advantages, challenges, and impacts of E-Learning, Blended Learning, and Hybrid Learning models in physics education through a systematic literature review of nationally accredited journal articles published between 2016 and 2025. Methodology: The research employed a literature review method, drawing on 55 articles from nationally accredited journals published between 2016 and 2025. Sources were obtained from Garuda Kemdikbud, Sinta, university journal portals, and open repositories. The selection process applied inclusion–exclusion criteria, keyword-based searches, and classification according to learning models (E-Learning, Blended Learning, and Hybrid Learning) in the context of physics education. Main Findings: The results indicate that E-Learning enhances students’ independence, creativity, and conceptual understanding through digital platforms such as Moodle, Google Sites, and Chamilo. Blended Learning effectively reduces misconceptions and improves learning outcomes by combining face-to-face and online instruction. Meanwhile, Hybrid Learning provides the most optimal academic achievement by integrating synchronous and asynchronous learning. Nevertheless, all three models face challenges related to infrastructure limitations, teacher preparedness, and students’ digital literacy. Novelty/Originality of this study: This study offers a comprehensive comparative analysis of E-Learning, Blended Learning, and Hybrid Learning in physics education, which has not previously been systematically reviewed. It enriches the body of knowledge by synthesizing empirical evidence, highlighting the strengths, weaknesses, and integration potential of the three models, and providing valuable insights for educators and policymakers in adopting effective digital learning strategies.